Physiological Effects of Backpack Packing, Wearing and Carrying on School Going Children - Gupta, Ishant; Kalra, Parveen; Iqbal, Rauf (Research into Design for Communities, Volume 1, 2017)
Thirty male school children from primary school, aged 12 years, were selected to carry backpacks of 10% body weight where 0% body weight was used as a baseline. Heart rate and blood pressure tests were conducted on the subjects. Subjects had walked on a treadmill for 20 min at each load condition at 1.1 m/s. This was done in both cases when subjects followed the normal pattern of packing and wearing and when they followed the American Occupational Therapy Association (AOTA) recommendations. Heart rate was recorded before, during and 5 min after walking on treadmill whereas blood pressures were measured before and immediately after trial, and at 3 and 5 min after every trial. The results showed a significant difference in heart rate, blood pressure and its recovery for 10% body weight load conditions before and after recommendations. The packing, carrying, wearing of backpack should be done as per the AOTA guidelines.